This study aims to analyze the effect of Debt to Equity Ratio (DER), Earnings Per Share (EPS), Debt to EBITDA, and EBITDA to Interest Expense (EBITDAIntExp) on Return on Equity (ROE) in manufacturing companies listed on the Indonesia Stock Exchange for th - Valentina Laura Febyan; Mohammad Sofyan; Muhammad Imron (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Earnings Per Share (EPS), Debt to EBITDA, and EBITDA to Interest Expense (EBITDAIntExp) on Return on Equity (ROE) in manufacturing companies listed on the Indonesia Stock Exchange for the 2024Q1–2025Q3 period. The background of this study is based on the importance of the manufacturing sector as one of the main pillars of the national economy and the existence of quite wide variations in profitability performance between companies in challenging economic conditions. This study uses a quantitative approach with panel data from 27 companies over six quarters, resulting in 162 observations. The analysis was conducted through panel data regression with the best model being the Fixed Effect Model. The results show that DER has a positive and significant effect on ROE, indicating that optimal use of debt can still drive increased returns on equity. EPS also has a positive and significant effect, indicating that the greater the profit available for each share, the stronger the company's ability to create value for shareholders. Conversely, Debt to EBITDA has a negative and significant effect on ROE, indicating that a high debt burden relative to the ability to generate operating income can depress profitability. EBITDAIntExp, on the other hand, has no significant effect on ROE. Simultaneously, all independent variables significantly influence ROE